2023
DOI: 10.21660/2023.111.3898
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Method of Calculating a Beam on a Two-Parameter Elastic Foundation

Sungat Akhazhanov

Abstract: When calculating beams lying on a solid elastic foundation, the simplest foundation model proposed by Winkler-Zimmerman is often used. This hypothesis has been repeatedly subjected to wellfounded criticism, because the deformation of the base occurs only in the area of the load applied to it. In order to clarify the Winkler-Zimmerman hypothesis, many authors have proposed other models that allow mitigating the disadvantage of this model to varying degrees. The paper deals with the method of obtaining an analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…They validated their solution by comparison with solutions for beam on Winkler and Pasternak foundations and found that their solutions were identical with solutions based on Winkler and Pasternak foundation for various boundary conditions of the beam. Other contributions on beam on elastic foundations are in Akhazhanov et al [17], [18], [19]; Huang et al [20]. Akhmediev et al [21] and Zhang et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…They validated their solution by comparison with solutions for beam on Winkler and Pasternak foundations and found that their solutions were identical with solutions based on Winkler and Pasternak foundation for various boundary conditions of the beam. Other contributions on beam on elastic foundations are in Akhazhanov et al [17], [18], [19]; Huang et al [20]. Akhmediev et al [21] and Zhang et al [22].…”
Section: Introductionmentioning
confidence: 99%